Development of Fermentation and Drying of Cocoa Beans Using a Rotary Fermentor-Drier - Abdul Haiyee, Zaibunnisa (2002)
Fermentation and drying processes are interrelated, but they are been carried out as separate entities requiring specific equipment at each stage. These processes are very labour intensive and time-consuming. Therefore, this study was designed to mechanically ferment and dry cocoa beans in a single unit using a rotary fermentor-drier as model study. The system would have the advantages of reducing the labour requirement, processing time and produce better or comparable quality to commercial cocoa beans. This study was carried out using a modified rotary drier with a capacity of 9 metric tonnes wet cocoa beans. Mixed hybrid wet cocoa beans were fermented in the rotary drier (4 days with turning after 48 hours for 5 minutes at O.5rpm). Samples were taken everyday and were immediately sun dried. Quality characteristics of the fermenting beans were monitored everyday and compared with the existing commercial method of fermentation in Indonesia (4 days with turning every 24 hours) and standard shallow box fermentation in Malaysia (6 days with turning at every 48 hours). The results obtained from cut test, fermentation index and colour fractionation showed that fermentation occurred significantly (p<0.05) more rapid in the rotary fermentor. Temperature development and bean colour also changed drastically in mechanical fermentation. There was no significant different (p>0.05) in acidity of the resultant beans from mechanical fermentation (4.45) and beans from commercial fermentation (4.6). However, shallow box (4.3) produced significantly (p<0.05) more acidic beans. Concentration of acetic acid was significantly (p<0.05) low in mechanically fermented beans and that of lactic acid were significantly (p<0.05) low in shallow box fermentation. Percentage of total polyphenol, which contributes to bitterness and astringency in cocoa beans, was also significantly (p<0.05) low in mechanically fermented beans (6.6) compared to other fermentation methods. Sensory evaluation results also showed that cocoa flavour were significantly (p<0.05) better in mechanically fermented beans. The mechanically fermented beans were then dried in the same rotary drier. The effect of fermentation time and drying temperature on the acidic quality of the resultant beans were investigated. The resultant bean quality was then compared with the control drying methods; sun drying (5 -7 days, 8 hours/day, turning every 12 hours) and commercial bed drier (31 hours, turning every 4 hours). Cocoa beans were fermented in the rotary fermentor-drier for 3 or 4 days. Initial drying temperature was set at 45°C, 55°C and 65°C until the bean moisture content reached 20-25%, followed by final drying at 65°C until bean moisture content reached 7.5%. Drying was stopped at night for 11-14 hours as a resting period. Air speed of the hot air and the rotating speed of the drier were kept constant, 5.2 ms·) and 0.5rpm, respectively. Generally, the beans produced from the rotary fermentor-drier were significantly (p<0.05) better quality than the beans produced from commercial bed drier in term of lower acidity and total polyphenol content and higher fermentation level. However, sun dried beans were significantly (P<0.05) better than beans from rotary fermentor-drier. The rate of drying increased with drying temperature; most rapid at 65°C followed by 55/65°C and 45/65°C for both 3 days and 4 days fermented beans. Sun dried beans have significantly (p<0.05) the highest level of fermentation, followed by 45/65°C, 55/65°C and 65°C within the same fermentation period. The 4 day fermented beans have significantly (p<0.05) lower percentage of total polyphenol compared to 3 day. Drying method and temperature also have a significant effect on the percentage of total polyphenol in the bean. The lowest total polyphenol content were in sun-dried beans, followed with 45/65°C, 55/65°C and 65°C. Sun dried beans have significantly (p<0.05) the lowest acidity compared to rotary and commercial bed drying. However, rotary drying temperature of 55/65°C produced the best acidic characteristic beans for both 3 and 4 days fermented beans. The concentration of acetic acid and lactic acid were also low in the beans dried at 55/65°C. Sensory evaluation results showed that cocoa flavour was better in 4 day fermented beans compared to 3 day. Therefore, 4 days rotary fermentation followed with drying temperature of 55/65°C would be recommended.